Workshop on Robot Competitions - Obdržálek, D.; Balogh, R.; Lugmayr, Artur (2018)
© 2018, IFIP International Federation for Information Processing. Robot competitions are more and more used as a tool for education as well as an entertainment activity. This workshop brings together organizers, participants, teachers, and other people interested to share best practices, discuss issues and possibly improve their work.